2022
DOI: 10.1038/s41598-022-16343-8
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 in the eye isomerizes by sunlight irradiation

Abstract: Photoisomerization of lipids has been well studied. As for the eyes, photoisomerization from 11-cis isomer to all-trans-retinal is well-known as the first step of the visual transduction in the photoreceptors. In addition to that, there would be other ocular lipids that undergo photoisomerization, which may be involved in ocular health and function. To explore any photoisomerizable lipids in the eyes, the nonirradiated and sunlight-irradiated eyeball extracts were subjected to liquid chromatography-mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The LC/MS method employed in this study was based on a reported study [18]. The dry lipids were reconstituted with pure methanol.…”
Section: Lc/ms Analysismentioning
confidence: 99%
“…The LC/MS method employed in this study was based on a reported study [18]. The dry lipids were reconstituted with pure methanol.…”
Section: Lc/ms Analysismentioning
confidence: 99%